The presence of neutrophil extracellular traps in different forms of pyoderma gangrenosum - Takaharu Ikeda; Tamihiro Kawakami; Kae Yokoyama; Yuka Nishibata; Sakiko Masuda; Utano Tomaru; Akihiro Ishizu (Frontiers Media S.A., 2023)
Abstract We demonstrated that there were abundant neutrophil extracellular traps (NETs) in the skin biopsies from various types of pyoderma gangrenosum (PG), based on the observation of extended and compact areas of immunolabeling of MPO and Cit H3 proteins. We suggest that neutrophils could undergo an aberrant NET formation in the lesions of PG patients, in the vast majority of idiopathic PG. We did not detect NETs in the skin ulcers of an antiphospholipid syndrome patient with a similar appearance to classical ulcerative PG, while rich NETs were found in the various types of PG. These findings suggest that the presence of NETs in skin tissues could serve as a marker for making differential diagnoses of various types of PG from other similar conditions.